Synthesis and characterization of alkoxy substituted thiourea with Curcuma longa as active layer in organic solar cell - Rafizah Rahamathullah (Terengganu: Universiti Malaysia Terengganu, 2016)
Organic solar cells based on single molecular system have attracted considerable attention because of their great potential to convert solar energy into electrical energy efficiently at low cost.